ANALISIS BEBAN KERJA UNTUK MENGETAHUI JUMLAH PEKERJA OPTIMAL KARYAWAN POLISHING 3 DENGAN MENGGUNAKAN METODE WORKLOAD ANALYSIS DI PT SURYA TOTO INDONESIA, TBK - Widodo, Tri; Fardiansyah, Ismail; Wiharta, Trisna (Journal Industrial Manufacturing, 2020)
ABSTRACTHuman resources are one of the most important components in a company. In the production process at the polishing section 3 PT. Surya Toto Indonesia still uses human labor and an ineffective workforce. So it is necessary to carry out research actions to determine the optimal number of workers. PT Surya Toto Indonesia is a company engaged in manufacturing which produces fittings, sanitary and kitchen set products. The objectives of this study include knowing the productive presentation of workers in a direct observation activity, to determine the standard time according to the observation time obtained, and to determine the optimal number of employees at Polishing 3.In this study, the optimal number of workers was calculated using Workload Analysis method where work measurement is carried out first to 10 workers using Work Sampling so that the standard time value will be obtained. The results of this study indicate that the yield of productive presentation is 71%. While the standard time obtained in this study was 13.53 minutes. The optimal number of employees is 8.85 people, which in this case can be equivalent to 9 people. So the workload analysis results show that the number of Polishing 3 employees is still not optimal.Keywords: Work Sampling, Workload Analysis, Optimal Number of Workers